Research of irinotecan stability in different methods of active loading into liposomes - Стадниченко, Александр Викторович; Краснопольский, Юрий Михайлович; Швец, Виталий Иванович; Ярных, Татьяна Григорьевна (ScienceRise: Pharmaceutical Science, 2016)
Irinotecan active encapsulation mechanisms into liposomes according “pH gradient” and “ammonium gradient” technologies were considered. Aim. Research of Irinotecan stability at typical for each “chemical gradient” technology pH values, and estimation of the impurities content correspondence with Draft quality control methods on " Related impurities” index, using Irinotecan conversion mechanism data. Methods. HPLC method was used for research, using Shimadzu LC-20 appliance, according to the USP impurities control method for semisynthetic product. Results. Impurity formation dynamics, similar to Irinotecane E lactone ring destruction product, was studied in 3 stages: at pH values 1.9, 5.0, and 5.5. Impurities formation wasn’t observed at pH 1.9, and Irinotecan was stable during observation period – within 12 hours. At pH 5.0, Irinotecan was stable during 12 hours, while impurities formation in quantity over specifications for the finished product was not observed. At pH 5.5, which is specific for the “ammonium gradient” technology, impurities formation was observed in one hour, which is more than 3 times exceeds permissible norms for impurities content in Liposomal Irinotecan finished dosage form. Conclusion. It has been found, that in terms of active compound stability, “pH gradient” technology is preferred compared to the “ammonium gradient” technology. After using “pH gradient” technology, “Related impurities” index corresponded to the Draft quality control methods. The obtained data were used for Irinotecan liposomal dosage form development for the further preclinical and clinical study